Medical Tourism in India: Issues, Opportunities and Designing Strategies for Growth and Development - Dawn , Suman Kumar; Pal, Swati (Gyan Management Journal, 2011)
Medical tourism is becoming a popular option for tourists across the globe. It encompasses µrir:.:·· and predominantly biomedical procedures, combined with travel and tourism. The term n;!: ;·. tourism has been coined by travel agencies and the mass media to describe the rapidly grc.· ... :· practice of travelling across international borders to obtain hi-tech medical care. Various co 1, ·:: .. :'. like Thailand, Malaysia, India, etc are promoting medical tourism aggressively. The key comp2:.
Keywords: Medical Tourism; SWOT; Yoga; Unani; Siddha; Ayurvedic; Naturopathy